BUDAYA SPIRITUAL SYEKH AULIA ABDUL GOPUR - Hermana Hermana (Patanjala: Journal of Historical and Cultural Research, 2009)
AbstrakKeberadaan makam keramat Syekh Aulia Abdul Gopur sangat berpengaruh terhadap kehidupan masyarakat sekitarnya dari segi sosial maupun ekonomi. Dari segi sosial kemasyarakatan, mereka mengenal adat istiadat para peziarah, sehingga dapat belajar dan memaknai kehidupan masyarakat pada umumnya. Para peziarah menginginkan perubahan taraf hidup, ketenangan jiwa, dan ini kebanyakan berhasil. Dengan motivasi seperti itu mereka mendatangi tempat keramat tersebut.  AbstractThe available of the Syekh Aulia Abdul Gopur’s holy grave is very influential toward the life of its surrounding community either from social sector or economic sector.From social community sector, the know the custom and behavior of visitor to a grave, so they learn and comprehend the society life. The visitors to a grave who want the charge of standard life, take the pacity of spirit and to develop in economic side or in their sprititual, By its motivision, the arrive that holy place.